VARIABEL YANG MEMPENGARUHI PEMILIHAN SALURAN DISTRIBUSI BAGI PETANI PRODUSEN SALAK (Studi pada petani salak di Desa Kresikan Kecamatan Gondangwetan Kabupaten Pasuruan) - Eri Yusnita Arvianti; Suntara Suntara (BUANA SAINS, 2009)
The aims of this research were to describe the market balance, goods balance, producer balance, and distributor balance influencing channel selection of zalacca producers in Pasuruan, and to analyze the dominant variable considered by the zallacca producer farmer in Pasuruan. The respondents were taken from the population of zalacca farmers by simple random sampling method resulting 50 respondents. The research results showed that market balance, goods balance, producer balance, and distributor balance variable simultaneously affected the selection of distribution channel. The distributor balance variable was the most dominant variable influencing the distribution channel selection